Analisis Pengaruh Kewajiban Penyediaan Modal Minimum (KPMM), Beban Operasional Pendapatan Operasional (BOPO), Financing To Deposit Ratio (FDR), dan Inflasi Terhadap Return On Asset (ROA) Pada Bank Umum Syariah di Indonesia Periode 2016-2019 - Al Iqbal, Muhammad Hilda; Budiyanto, Iwan (MALIA: Journal of Islamic Banking and Finance, 2020)
This study aims to analyze and obtain empirical evidence regarding the effect of KPMM, BOPO, FDR, and Inflation on ROA in Islamic Commercial Banks in Indonesia for the period of 2016-2019. The method used is Multiple Linear Regression Analysis with the analysis techniques F Test, R2 Test, and t Test. Based on the results of testing and discussion, the results of KPMM, BOPO, FDR, and Inflation simultaneously have a significant effect on the Return on Assets (ROA) of Islamic Commercial Banks in Indonesia. Partially, BOPO and FDR have a significant effect on Return on Assets (ROA). Meanwhile, KPMM and Inflation do not have a significant effect on Return on Assets (ROA) at Islamic Commercial Banks in Indonesia.